Exploring the Antimycobacterial Potential of Podocarpusflavone A from Kielmeyera membranacea: In Vitro and In Vivo Insights - Marlon Heggdorne de Araujo; Salomé Muñoz Sánchez; Thatiana Lopes Biá Ventura Simão; Natalia Nowik; Stella Schuenck Antunes; Shaft Corrêa Pinto; Davide Sorze; Francesca Boldrin; Riccardo Manganelli; Nelilma Correia Romeiro; Elena B. Lasunskaia; Fons J. Verbeek; et al. (Pharmaceuticals)
Background/Objectives: Tuberculosis (TB) is one of the leading infectious causes of death worldwide, highlighting the importance of identifying new anti-TB agents. In previous research, our team identified antimycobacterial activity in Kielmeyera membranacea leaf extract; therefore, this study aims to conduct further exploration of its potential. Methods: Classical chromatography was applied for fractionation and spectrometric techniques were utilized for chemical characterization. For in vitro tests, samples were assessed against Mycobacterium tuberculosis and Mycobacterium marinum. The toxicity and efficacy of active samples were evaluated in vivo using different zebrafish models. Chemogenomics studies were applied to predict the isolated active compound’s potential mode of action. Results: We performed fractionation of K. membranacea ethanolic extract (EE) and then its dichloromethane fraction (DCM), and the biflavonoid podocarpusflavone A (PCFA) was isolated and identified as a promising active compound. The EE and PCFA were found to be non-toxic to zebrafish larvae and were able to inhibit M. tuberculosis growth extracellularly. Additionally, PCFA demonstrated antimycobacterial activity within infected macrophages, especially when combined with isoniazid. In addition, the EE, DCM, and PCFA have shown the ability to inhibit M. marinum’s growth during in vivo zebrafish larvae yolk infection. Notably, PCFA also effectively countered systemic infection established through the caudal vein, showing a similar inhibitory activity profile to rifampicin, both at 32 µM. A reduction in the transcriptional levels of pro-inflammatory cytokines confirmed the infection resolution. The protein tyrosine phosphatase B (PtpB) of M. tuberculosis, which inhibits the macrophage immune response, was predicted as a theoretical target of PCFA. This finding is in agreement with the higher activity observed for PCFA intracellularly and in vivo on zebrafish, compared with the direct action in M. tuberculosis. Conclusions: Here, we describe the discovery of PCFA as an intracellular inhibitor of M. tuberculosis and provide evidence of its in vivo efficacy and safety, encouraging its further development as a combination drug in novel therapeutic regimens for TB.